Peran Farmasi dalam Skrining Kadar Glukosa Darah Sewaktu Pada Masyarakat Desa Kabul Sebagai Deteksi Dini Diabetes Melitus - Sri Winarni Sofya; Ayudia Cipta Khairani; Mia Ariasti; Lalu Busyairi Muhsin; Baiq Fitri Yunita (Universitas Mataram, 2026)
Diabetes mellitus often remains undetected in its early stages because its symptoms are nonspecific; therefore, community-based screening is needed to identify individuals at risk. This community service activity aimed to support early detection of diabetes mellitus through random blood glucose testing among residents of Kabul Village, Praya Barat Daya District, Central Lombok. The activity involved 25 participants aged 18 years or older and comprised preparation, glucometer-based testing, delivery of individual results, and brief health education. Data were analyzed descriptively according to random blood glucose categories. The results showed that 22 participants (88%) had normal glucose levels, one participant (4%) was classified as prediabetic, and two participants (8%) were suspected of having diabetes mellitus. These findings indicate that random blood glucose testing can serve as a practical initial screening method for identifying at-risk individuals. Participants with above-normal results should undergo confirmatory examination at a healthcare facility.